ChemInform Abstract: Photocatalytic CO2 Reduction by TiO2 and Related Titanium Containing Solids. Issue 19 (18th April 2013) - Dhakshinamoorthy, Amarajothi; Navalon, Sergio; Corma, Avelino; Garcia, Hermenegildo
Abstract Review: 147 refs.